Firm Level Characteristics and Stock Returns: Evidence from Selected Insurance Companies Listed on the Dhaka Stock Exchange - Barua, Senjuti (Asian Economic and Financial Review, 2020)
This study focuses on investigating several firm level characteristics that determine the stock returns of forty-five insurance companies listed on the Dhaka Stock Exchange (DSE), Bangladesh. Very few studies have been conducted using panel data analysis on the DSE, or other emerging stock markets, compared to developed stock markets. Being a country facing huge risks caused by numerous natural disasters throughout the year, Bangladesh has the opportunity to overcome these risks through both life and general insurance. This study aims to investigate the impact of six firm level characteristics on the stock returns of selected insurance companies listed on the DSE from 2009 to 2019. To analyze the influences of these factors, panel data analysis for balanced panel data (5,577 observations) has been applied while incorporating some relevant tests, which confirm that the fixed-effect model is more suitable than the random-effect model. The study revealed that the positive influences of turnover by value and volume of shares traded are significant, and the negative influence of firm size is also significant. However, the positive impact of highest closing price per month, firm beta and liquidity factors on stock returns is insignificant. The results of the study will add to the existing literature by supporting or contradicting different facts.